Constructing college students’ musical cultural identity and self-confidence under cross-regional cultural integration: an integrative study based on cultural connections and multicultural experiences - Huijing, Xiong; Yunlong, Hou; Yuyao, Liang; Xinyi, Cao (Frontiers in Psychology, 2026)
This study investigated the complex interplay between multicultural experiences (MCEs) and hometown music-cultural connection (HMC) in shaping the musical cultural self-confidence of Chinese college students. Through three studies (N₁ = 432, N₂ = 222, N₃ = 85), we found that while real-world MCEs were associated with lower explicit confidence, this relationship was masked by a positive indirect effect through strengthened HMC. However, this mediation was not observed when assessing implicit affective associations. Crucially, an experimental manipulation of MCEs yielded no significant effects, yet HMC consistently predicted higher confidence across both explicit and implicit cognitive measures. These results demonstrate that HMC is a stable personal resource sustaining cultural confidence, whereas the influence of MCEs is more nuanced and may not be easily induced in the short term. The findings highlight the importance of fostering deep cultural attachments for identity stability in an increasingly mobile world.